Comparison of autohydrolysis and ionic liquid 1-butyl-3-methylimidazolium acetate pretreatment to enhance enzymatic hydrolysis of sugarcane bagasse. (January 2017) - Hashmi, Muzna; Sun, Qining; Tao, Jingming; Wells, Tyrone; Shah, Aamer Ali; Labbé, Nicole; Ragauskas, Arthur J.
Graphical abstract: Highlights: Two eco-friendly pretreatments were investigated to improve the sugar yield. Improved hemicelluloses recovery after [C4 mim][OAc] pretreatment. The reduced crystallinity after [C4 mim][OAc] pretreatment. The improved kinetics with higher sugar yields from [C4 mim][OAc]-treated bagasse. Abstract: The aim of this work was to evaluate the efficiency of an ionic liquid (IL) 1-butyl-3-methylimidazolium acetate ([C4 mim][OAc]) pretreatment (110 °C for 30 min) in comparison to high severity autohydrolysis pretreatment in terms of delignification, cellulose crystallinity and enzymatic digestibility. The increase in severity of autohydrolysis pretreatment had positive effect on glucan digestibility, but was limited by the crystallinity of cellulose. [C4 mim][OAc] pretreated sugarcane bagasse exhibited a substantial decrease in lignin content, reduced cellulose crystallinity, and enhanced glucan and xylan digestibility. Glucan and xylan digestibility was determined as 97.4% and 98.6% from [C4 mim][OAc] pretreated bagasse, and 62.1% and 57.5% from the bagasse autohydrolyzed at 205 °C for 6 min, respectively. The results indicated the improved digestibility and hydrolysis rates after [C4 mim][OAc] pretreatment when compared against a comparable autohydrolyzed biomass.